2007
DOI: 10.2165/00003088-200746050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Animal-to-Human Extrapolation of the Pharmacokinetic and Pharmacodynamic Properties of Buprenorphine

Abstract: The different values of the drug-specific pharmacodynamic parameters are consistent with the different opioid mu receptor subtypes involved in the antinociceptive and respiratory depressant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Based on allometric principles biological time periods, t, are dependent on a scaling factor in the power function of ¼ (t=θ · body weight 1/4 ) [11]. Although there has been a clear correlation to body weight in scaling pharmacodynamic models [15][16][17][18][19] the estimates of the exponent of the correlation have in most cases differed from the theoretical value of ¼. Interestingly, the exponent for red blood cell and red blood cell precursor life spans were estimated to 0.124-0.148 [15], which is similar to the exponent value of 0.158 that would be used to scale the here estimated MTT for white blood cells of 52.8 h in a 300 g rat to a value of 125 h in a 70 kg patient. The estimated feedback factor γ was 0.149 in rats, a value that is in the same range as those earlier determined in patients (0.121-0.239) [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on allometric principles biological time periods, t, are dependent on a scaling factor in the power function of ¼ (t=θ · body weight 1/4 ) [11]. Although there has been a clear correlation to body weight in scaling pharmacodynamic models [15][16][17][18][19] the estimates of the exponent of the correlation have in most cases differed from the theoretical value of ¼. Interestingly, the exponent for red blood cell and red blood cell precursor life spans were estimated to 0.124-0.148 [15], which is similar to the exponent value of 0.158 that would be used to scale the here estimated MTT for white blood cells of 52.8 h in a 300 g rat to a value of 125 h in a 70 kg patient. The estimated feedback factor γ was 0.149 in rats, a value that is in the same range as those earlier determined in patients (0.121-0.239) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Model-based pharmacodynamic scaling has for example been performed for recombinant human erythropoietin [15], 5-Ht 1A receptor mediated responses, i.e. hypothermia and cortisol responses [16], respiratory depressant and antinociceptive effects [17], thromboxane B 2 and prostaglandin E 2 dynamics [18] and muscle relaxation [19]. The low number of successful cases of pharmacodynamic scaling may partly be because often parameters used in the scaling are based on empirical models in contrast to physiologybased or mechanistic models.…”
Section: Introductionmentioning
confidence: 99%
“…This approach confers advantages in that the structure and parameters of the model can be related to prior mechanistic data, the concentration response can be related to any in vitro measures of pharmacology, and extrapolation of preclinical findings to the clinical outcome can in principle be facilitated. For example, a mechanistic PK-PD approach was used previously to show that buprenorphine-specific PD parameters such as binding of the drug to the target were similar in rats and humans (40). In addition, it has been found that although concentration-response data can translate well between species, the dose response can be very different due to interspecies PK differences (23).…”
Section: Discussionmentioning
confidence: 99%
“…Allometric scaling of drug pharmacokinetic properties and biological system-specific parameters has been used in translational investigations, with reasonable degree of success, to predict drug effects in humans (Yassen et al 2007;Zuideveld et al 2007). But, pharmacodynamic properties are more difficult to scale compared to pharmacokinetic properties, since pharmacodynamic parameters are often not related to bodyweight (e.g., receptor (Kvernmo et al 2006(Kvernmo et al , 2008 and on prolactin in animals and human (Ben Jonathan et al 2008).…”
Section: Use Of the Structural Preclinical Pkpd Model To Finally Predictmentioning
confidence: 99%